Contribution of Supervision and Professional Development to the Performance of Guidance and Counseling Teachers - Yenni Elfira; Herman Nirwana; Marjohan Marjohan (Journal of Leadership, Organization, Vision, and Administration, 2025)
This study aims to describe guidance and counseling supervision, professional development of guidance and counseling teachers, and the performance of guidance and counseling teachers, as well as to analyze the contribution of supervision and professional development to guidance and counseling teacher performance. The study used a quantitative approach with descriptive methods and multiple correlation analysis on 115 guidance and counseling teachers of junior high schools (SMP), senior high schools (SMAN), and vocational schools (SMKN) in Kota Padang Panjang, and Tanah Datar Regency who were selected through purposive sampling. The research instrument was a Likert scale. The research results show that guidance and counseling supervision and professional development have been proven to provide a positive and significant contribution to the performance of guidance and counseling teachers, which shows that the combination of good supervision and optimal professional development is able to improve the overall performance of guidance and counseling teachers.